Consensus method study for a multi-agent system with faults - Wang, Donghai (Nanyang Technological University, 2023)
In recent years, the development and intersection of various disciplines, such as biological sciences and control sciences, have led to the widespread application of multi-agent systems in numerous fields, including aerospace, military, and industry. The consensus problem, a basic issue in the control design of multi-agent systems (MAS), has become a core research topic. However, due to uncontrollable factors encountered during the practical operation of MAS, agent failures are unavoidable. This poses the challenge of ensuring consensus in fault-prone MAS. This study is of consensus methods for MAS with faults, aiming to develop effective strategies for maintaining system performance and stability despite agent failures. Through simulation results, the performance of our proposed methods in achieving consensus and maintaining optimal operation in MAS with faults is demonstrated. This research contributes to the advancement of coordinated control techniques and paves the way for more resilient and adaptable MAS in a variety of applications.